3D Nitrogen‐Doped Graphene Encapsulated Metallic Nickel–Iron Alloy Nanoparticles for Efficient Bifunctional Oxygen Electrocatalysis. Issue 18 (13th March 2020) - Wang, Zhaoyang; Liao, Xiaobin; Lin, Zifeng; Huang, Fuzhi; Jiang, Yalong; Owusu, Kwadwo Asare; Xu, Lin; Liu, Ziang; Li, Jiantao; Zhao, Yan; Cheng, Yi‐Bing; Mai, Liqiang
Abstract: Invited for the cover of this issue is Liqiang Mai and co‐workers at Wuhan University of Technology. The image depicts Ni3 Fe alloy nanoparticles encapsulated in N‐doped graphene as an efficient bifunctional oxygen electrocatalyst toward rechargeable Zn‐air batteries, which is expected to drive the electric vehicle. Read the full text of the article at 10.1002/chem.201904722 . Abstract : " Herein, a 3D porous nitrogen‐doped graphene encapsulated metallic Ni3 Fe alloy nanoparticles aerogel was prepared by a facile hydrothermal assembly and subsequent calcination, which exhibited outstanding catalytic activities ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 4044 ff. (DOI: 10.1002/chem.201904722 ).